The Preface and Subject Matter of Cyril of Alexandria’s De Adoratione - Crawford, Matthew R. (The journal of theological studies, 2013)
Cyril of Alexandria’s treatise De adoratione is unique among his writings in that it lacks a preface or prologue in the edition of the work found in Patrologia Graeca. Although in 1989 Georges-Matthieu de Durand pointed to the existence of a preface to De adoratione preserved in an eleventh-century manuscript in the Bodleian library, subsequent studies of Cyril’s corpus have failed to take note of Durand’s find. Moreover, Durand apparently did not realize that this same preface also survives in a single Syriac manuscript held by the British Library, which predates the Bodleian Greek manuscript by several centuries. In this article I provide a transcription of the Greek and Syriac recensions along with an English translation, and then consider the significance of this passage for interpreting De adoratione. The preface indicates the treatise should be read not primarily in the light of Jewish–Christian power struggles in late antique Alexandria, but rather as a contribution to the ascetic project being undertaken at the time in the Egyptian desert. Hence, Cyril’s attempt to use Scripture to provide ‘moral guidance’ in De adoratione should be seen as a complementary mode of exegesis to the ‘more dogmatic exegesis’ of his well-known Johannine commentary.